The Correlations among English Learning Motivation, Learning Styles, and English Mastery of Senior High School Students Taking an English Course in Palembang - Raty Rusmiana (Relawan Jurnal Indonesia, 2022)
Abstract: The aim of this study was to investigate the correlations among English learning motivation, learning styles, and English mastery of senior high school students taking an English course in Palembang. In this correlational study, the data were collected through test and questionnaires. English learning motivation questionnaire, learning styles questionnaire, and English test were administered to 102 senior high school students taking an English course in Palembang. The data were analyzed by using correlational and regression analyses. The results showed that there were no significant correlations between English learning motivation and English mastery, between learning styles and English mastery, and between predictor variables and criterion variable . However, further calculation using multiple regression analysis showed that the contribution of instrumental motivation was 6.4 %. It implied that there was a little contribution of English learning motivation to students’ English mastery. On the other hand, the results showed that none of the aspects of learning styles significantly contributed to English mastery. Keywords:English learning motivation, learning styles, English mastery